Higher Education, Productivity Revelation and Performance-pay Jobs - Jisun Baek; Wooram Park (KDI Journal of Economic Policy, 2018)
This paper examines the differences between the subsequent careers of high school and college graduate workers based on a direct role of college graduation with regard to the revelation of workers' individual abilities. Using NLSY79, we document a positive relationship between off-the-job training/performance-pay jobs and ability for high school graduates at the early stages of their careers. However, this relationship is less prominent for college graduates. Moreover, we show that high ability is associated with more jobs, which reflects higher job mobility, only for high school graduates. We argue that these patterns are the result of productivity-revealing behavior of high school graduates, whose individual abilities, unlike college graduates, is not observed precisely at the beginning of their careers.
Keywords: I20; J24; 330; Productivity Revealing; Off-the-job Training; NLSY79; Performance-pay Jobs; Job Mobility; College Education